Different genetic factors underlie fear conditioning and episodic memory. (August 2015) - Fredrikson, Mats; Annas, Peter; Hettema, John M.
<x xml:space="preserve">Abstract</x> Objective Fear conditioning seems to account for the acquisition of post-traumatic stress disorder, whereas conscious recall of events in aftermath of trauma reflects episodic memory. Studies show that both fear conditioning and episodic memory are heritable, but no study has evaluated whether they reflect common or separate genetic factors. To this end, we studied episodic memory and fear conditioning in 173 healthy twin pairs using visual stimuli predicting unconditioned electric shocks. Methods Fear conditioning acquisition and extinction was determined using conditioned visual stimuli predicting unconditioned mild electric shocks, whereas electrodermal activity served as the fear learning index. Episodic memory was evaluated using cued recall of pictorial stimuli unrelated to conditioning. We used multivariate structural equation modeling to jointly analyze memory performance and acquisition as well as extinction of fear conditioning. Results Best-fit twin models estimated moderate genetic loadings for conditioning and memory measures, with no genetic covariation between them. Conclusion Individual differences in fear conditioning and episodic memory reflect distinct genetically influenced processes, suggesting that the genetic risk for learning-induced anxiety disorders includes at least two memory-related genetic factors. These findings are consistent with the facts that the two separate learning forms are distant in their evolutionary development, involve different brain mechanisms, and support that genetically independent memory systems are pivotal in the development and maintenance of syndromes related to fear learning.